2006
DOI: 10.1253/circj.70.502
|View full text |Cite
|
Sign up to set email alerts
|

Arrhythmogenesis in the Short-QT Syndrome Associated With Combined HERG Channel Gating Defects

Abstract: he short-QT syndrome constitutes a new primary electrical abnormality associated with sudden cardiac death. 1,2 A part of the disorder has been linked to gain of function mutations in the cardiac channel of rapidly activating delayed rectifier currents (IKr), HERG (KCNH2). 3 Heterogeneous abbreviation of the action potential duration (APD) in different cell types spanning the ventricular wall seems to create the substrate for the genesis of ventricular arrhythmia in the short-QT syndrome, as is proposed for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 24 publications
2
22
0
Order By: Relevance
“…It is also interesting to notice how the reversal potential is shifted to more positive potentials in N588K compared to WT channels. This is consistent with earlier findings and in silico simulations have demonstrated how such a change in selectivity increase the chance of evoking early after depolarisations (EAD's) [14,21,25]. Since it is still an open question whether the β-subunit KCNE2 is a part of native I Kr current co-expression experiments with HERG-N588K and KCNE2 were also performed.…”
Section: Discussionsupporting
confidence: 90%
“…It is also interesting to notice how the reversal potential is shifted to more positive potentials in N588K compared to WT channels. This is consistent with earlier findings and in silico simulations have demonstrated how such a change in selectivity increase the chance of evoking early after depolarisations (EAD's) [14,21,25]. Since it is still an open question whether the β-subunit KCNE2 is a part of native I Kr current co-expression experiments with HERG-N588K and KCNE2 were also performed.…”
Section: Discussionsupporting
confidence: 90%
“…An alternative to animal models is to use in silico models of the N588K mutation (283,681,712). These models have reproduced the shorter action potential duration and QT interval; however, the earlier models did not reproduce the altered dispersion of repolarization or the taller T-waves typical of SQTS1.…”
Section: Models Of Sqtsmentioning
confidence: 99%
“…Computer simulations that mimic the major kinetic changes to I Kr , I Ks and I K1 of the major SQT1-3 mutations have shown accelerated repolarisation convincingly at cell and tissue levels [26,27,60,[75][76][77], though with changes to T-wave morphology more accurately reproduced for SQT2 [60] and SQT3 [27] variants than for SQT1 [75,76]. At the single cell level, AP shortening in simulated SQT1 and SQT2 is heterogeneous, with mid-myocardial AP repolarisation more greatly affected than that in epicardial or endocardial cells [60,75,76].…”
Section: Mechanisms Of Arrhythmogenesismentioning
confidence: 99%
“…This is attributable to differences in AP morphology between the two cell types and may lead to increased heterogeneity between ventricular and Purkinje fibre repolarisation in SQT1, which could feasibly contribute to prominent U-waves seen in some SQTS patients [47,49,52]. One simulation study has suggested that hERG gating defects due to the N588K mutation might facilitate early after-depolarisations in SQT1 [77], with reduced hERG 'tail currents' [78] and altered response to 'premature' stimuli in vitro [52]. Our most detailed simulation work to-date has been for V307L-KCNQ1-linked SQT2.…”
Section: Mechanisms Of Arrhythmogenesismentioning
confidence: 99%